Strategi Pengembangan Kawasan Wisata Pantai Lombang Kabupaten Sumenep - Mohammad Zainul Arief (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
Sumenep Regency has cultural diversity, which is supported by a culture of social life that is different from other districts in Madura. In accordance with government policy in developing tourism, especially in Sumenep Regency, it is necessary to have a guideline for a directed and integrated development plan. Tourist objects that are interesting to visit besides being good attractions also need an orderly and neat arrangement, especially from a physical point of view. In addition, the need for tour packages that are supported by travel agencies, travel agent services, and tour guides. In this study